(untitled) (Eurasian Journal of Ecology, 2016)
As a result of researches of the fauna of sandy deserts of Kazakhstan 155 species of Heteroptera are revealed. Among them by fodder specialization prevail polyphytophages (61 species), wide oligophytophages - 41 species, narrow oligophytophages - 21 species, monophytophages - 3 species, zoophages - 25 species, zoophytophages - 3 species, food connections are not found out at Periphima batesoni.